Can the Prognosis of Cardiac Resynchronization Therapy Be Predicted by Gated SPECT?. (October 2015) - Qin, Shengmei; Shi, Hongcheng; Su, Yangang; Chen, Shuguang; Pan, Wenzhi; Ge, Junbo
<x xml:space="preserve">Abstract</x> Purpose The aim of this study was to evaluate the role of gated myocardial perfusion SPECT (GMPS) phase parameters (phase SD and histogram bandwidth) in predicting the short-term response to cardiac resynchronization therapy (CRT) as left ventricle (LV) remodeling and the long-term effect as all-cause mortality or cardiac transplantation and hospitalization for heart failure. Patients and Methods This prospective observational study included 63 consecutive patients undergoing CRT from May 2008 to April 2014. Before CRT, patients underwent evaluation of New York Heart Association functional class, standard 12-lead ECG, 99mTc-MIBI GMPS, and 2-dimensional echocardiography. The patients were grouped according to complete left bundle-branch block (CLBBB). Follow-up was done every 6 months after pacemaker implantation. The short-term end point was reverse LV remodeling in 6 to 12 months follow-up, and the long-term primary end point was all-cause mortality or cardiac transplantation. The secondary end point was hospitalization for heart failure. Results Reverse LV remodeling showed in 60.9% (39/63) patients (74.5% CLBBB [35/47] vs 25.0% non-CLBBB [4/16], P < 0.001). Phase SD less than 55 degrees, CLBBB, and left atrium diameter were independent predictive factors for reverse LV remodeling. At a median follow-up of 39.76 months, there were 17 deaths and 2 transplantations (17.0% CLBBB vs 68.8% non-CLBBB, P < 0.001). Seventeen patients required hospitalization more than once for heart failure, and 2 underwent heart transplantation (14.9% CLBBB vs 62.5% non-CLBBB, P < 0.001). Multivariate logistic regression showed that only CLBBB was an independent predictive factor for both end points. Conclusions The GMPS parameters were not independent predictive factors for all-cause mortality or cardiac transplantation and hospitalization for heart failure.